(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2021)
A novel, accurate, precise, specific, sensitive and robust RP-HPLC method was developed and validated for the determination of Fedratinib using Analytical Quality by Design (AQbD) approach which was mentioned in ICH Q8 (R2) guidelines. By implementing QbD in HPLC methods, ruggedness and robustness will be verified early in the stage of method development to ensure performance of the method over the life time of the product. Design Expert® (12.0.12.0) modelling software (Stat-Ease Inc., Minneapolis, MN, USA) was used for Response surface methodology (RSM). Plackett-Burman design was employed for the factor screening studies to identify the critical method parameters (CMP) affecting the critical quality attributes (CQA). The selected CMP’s were systematically optimized using Central-composite design (CCD). Statistical analysis of the responses was done by applying analysis of variance. Chromatographic separation was accomplished on Agilent C18 (150×4.6 mm, 5 µm) column and PDA-UV detection was set at 268 nm. The optimized and predicted data from Design Expert software consisted of mobile phase Acetonitrile: 0.1% OPA buffer pH 4.18 (43: 57 % v/v), pumped at a flow rate of 0.967 mL /min gave the highest desirability of 1. The developed chromatographic method was validated as per ICH Q2 (R1) guidelines and found to be linear over concentration range of 15-90 µg/mL with correlation coefficient of 0.999. Degradation studies were performed by exposing the drug to various stress conditions as per ICH Q1A (R2) guidelines and significant degradation was found in acidic condition.